Studi Fenomenologi: Pelaksanaan Patient Center Care Perspektif Pasien dan Perawat di RS dr. Dradjat Prawiranegara Serang - Eka Ernawati; Milawati Lusiani (Faletehan Health Journal, 2019)
Nursing service is one of the requirements that must be implemented in a health care service provider in Indonesia. Patient-centered care (PCC) is an approach that fosters patient-centered health care. It is an approach to fostering reciprocal relationships between service providers and patients. The aim of the study was to determine the phenomenon of the implementation of PCC in the perspective of patients and nurses. The design in the study used a descriptive narrative qualitative design. The results of the study found the themes that emerged from patient participants consisted of: lack of health information received and treatment that lacked care in care; patients are not familiar with their condition and suggestions with traditional medicine; family support needed by patients. While the themes that emerged from nurse participants consisted of: Less recognition of PCC and less optimal nursing care; special team for patient referrals / referrals to the next level; delivering health information from health workers. This study concluded that it was necessary to increase the understanding of PCC to service providers and patients. So that hospitals can form a special referral system for patients to further services.